Bok: real killer or bystander with non-apoptotic roles? - Caden G. Bonzerato; Richard J. H. Wojcikiewicz (Frontiers in Cell and Developmental Biology, 2023)
Bcl-2-related ovarian killer, Bok, was first labeled “pro-apoptotic” due to its ability to cause cell death when over-expressed. However, it has become apparent that this is not a good name, since Bok is widely expressed in tissues other than ovaries. Further, there is serious doubt as to whether Bok is a real “killer,” due to disparities in the ability of over-expressed versus endogenous Bok to trigger apoptosis. In this brief review, we rationalize these disparities and argue that endogenous Bok is very different from the pro-apoptotic, mitochondrial outer membrane permeabilization mediators, Bak and Bax. Instead, Bok is a stable, endoplasmic reticulum-located protein bound to inositol 1,4,5 trisphosphate receptors. From this location, Bok plays a variety of roles, including regulation of endoplasmic reticulum/mitochondria contact sites and mitochondrial dynamics. Therefore, categorizing Bok as a “killer” may well be misleading and instead, endogenous Bok would better be considered an endoplasmic reticulum-located “bystander”, with non-apoptotic roles.